The shock and release behavior of an aerospace-grade cured aromatic amine epoxy resin - Hazell, Paul J.; Stennett, Christopher; Cooper, G. (Wiley, 2008)
Knowing the dynamic behavior of polymer materials that are used in the construction of fiber-reinforced composite materials is particularly important for such materials that are subjected to impact. In this work, we have conducted a number of plate-impact experiments on a commercially important aromatic amine epoxy resin that is used in the construction of carbon fiber composite materials. The measured Hugoniot in shock velocity–particle velocity space was Us = 2.65 + 1.55 up ( ρ0 = 1.141 g/cc), and is similar to the measured Hugoniots of other resins presented by different researchers. We have also measured the longitudinal stress in the shocked material and shown, in common with other polymers, that above a threshold stress, an increase in shear strength with impact stress is observ
Keywords: Shock behaviour; Hugoniot; polymers; steric effects